1983
DOI: 10.1084/jem.157.2.583
|View full text |Cite
|
Sign up to set email alerts
|

B cell growth factors and B cell differentiation factor from human T hybridomas. Two distinct kinds of B cell growth factor and their synergism in B cell proliferation.

Abstract: Discovery and use ofT cell growth factor, interleukin 2 (IL-2), 1 have made it possible to immortalize functioning T cells and have facilitated studies on the activation, function, and antigen recognition of T cells (1-3). Human and murine neoplastic T cells secreting IL-2 have been particulary useful for the isolation and molecular characterization of IL-2 (4, 5).Recent studies with successful long-term culture of murine or human B cells (6, 7) as well as with short-term B cell culture (8) have suggested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1
3

Year Published

1985
1985
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(50 citation statements)
references
References 17 publications
(8 reference statements)
0
46
1
3
Order By: Relevance
“…Second, B cells and B cell blasts cannot absorb IL-2 activity in the murine system (15). Third, highly purified IL-2 or IL-2-containing supernatants from T-T hybridomas have little effect on B cell proliferation in the absence or presence of polyclonal B cell activators (35)(36)(37). Fourth, it has been demonstrated (14) that clonal expansion and differentiation of individual hapten-specific B cells require soluble factors distinct from IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…Second, B cells and B cell blasts cannot absorb IL-2 activity in the murine system (15). Third, highly purified IL-2 or IL-2-containing supernatants from T-T hybridomas have little effect on B cell proliferation in the absence or presence of polyclonal B cell activators (35)(36)(37). Fourth, it has been demonstrated (14) that clonal expansion and differentiation of individual hapten-specific B cells require soluble factors distinct from IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…IL1B was shown to enhance the production of immune-related molecules, such as nitric oxide, acute-phase proteins, cytokines, and chemokines (Arend et al 2008). IL6 has multiple functions, such as stimulation of antibody synthesis by B cells (Okada et al 1983) and the differentiation of monocytes from dendritic cells to macrophages (Chomarat et al 2000). We have reported that the injection of birds with LPS enhanced the expression of both AvBDs and proinflammatory cytokines, IL1B and IL6, in the vagina (Abdel Mageed et al 2008, Nii et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Many of these Stat3-activating cytokines, such as IL-2, IL-10, IL-6, and IL-21, have been implicated in the terminal differentiation of B cells into antibodysecreting plasma cells. [18][19][20][21] We recently showed by transcriptional profiling that, compared with B cells, plasma cells selectively retain Stat3 and both chains of the IL-6 receptor, IL-6R␣, and gp130, whereas inhibitors of Stat3 signaling, including PIAS3 and SOCS3, are absent or down-regulated in plasma cells, as were Stat4, Stat5a/b, and Stat6. 22 These results strongly implied an important role for Stat3 in plasma cell formation.…”
Section: Introductionmentioning
confidence: 99%